HAK GANTI RUGI PENUMPANG DAN TANGGUNG JAWAB MASKAPAI PENERBANGAN TELAAH UNDANG-UNDANG PENERBANGAN INDONESIA - Annalisa Yahanan; Kamal Halili Hassan (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2010)
Air transportation is more interested in the various activities. As a flight service consumer, their rights are protected by law, both in the Law No. 1 of 2009 about Aviation and the Law No. 8 of 1999 about Consumer Protection. If passengers are at a lower position compared with airlines in the relationship between consumers and producer. Passengers tend to prefer to take no action if harmed by the airline. One of passenger rights of the most fundamental is the right to compensation effect using airline service as a carrier. When damaged by the airlines, passengers prefer to take no action event hough he has the rights to obtain compensation. This research analyzes about how the air carriers liability of damaged passengers and the concept of liability is applied in the Aviation Act. The data which is used in this research is secondary data and is supported by primary data and are distributed 100 questionnaires to domestic passengers which using purposive sampling. The purpose of this research to know whether the Aviation Act regulate expressly the air carrier liability for losses due to passengers using the airlines and analyze the concept of liability is used in theAviation Act. The results showed that the LawAviation is liable for the loss of passengers which is devided in 4 (four) articles, namely: the loss of passengers who died, permanent disability or injury; damaged or lost register baggage ; damaged or lost cabin baggage; and delaying in passengers, baggage and cargo carrier. There are 3 (three) concepts of legal liability in theAviation Act, they are; the concept of legal liability based on fault; concept of legal liability based on presumption (presumption of Liability); and the concept based on absolute liability. Recommendations of this research are creating immediately regulation of implementing the Aviation Act which related to compentation rights, need for increasing the empowerment of passengers to claim their rights, standard clause in the tickets, need repairing.